Atlantic salmon (Salmo salar) and brown trout (Salmo trutta) differ in their suitability as hosts for the endangered freshwater pearl mussel (Margaritifera margaritifera) in northern Fennoscandian rivers. (24th May 2017) - Salonen, Jouni K.; Luhta, Pirkko‐Liisa; Moilanen, Eero; Oulasvirta, Panu; Turunen, Jarno; Taskinen, Jouni
Abstract: European populations of the freshwater pearl mussel (FPM, Margaritifera margaritifera ) have collapsed across much of the species' geographic range and, despite many types of conservation intervention, the number of successful restoration efforts has been low. The goal of this study was to determine whether there were population‐specific differences in the suitability of Atlantic salmon ( Salmo salar ) and brown trout ( S. trutta ) as hosts for the parasitic glochidium larvae of FPM. We predicted that such differences would depend on the historical occurrence of these salmonid species in FPM habitats. We studied the potential host specificity both in the field and in laboratory by exposing salmonid fish to FPM glochidia originating from nine populations in different types of streams and rivers within three large river basins in northern Fennoscandia. The exposures showed remarkable population‐specific differences in the suitability of host species. In large main channels, previously colonised by Atlantic salmon but mostly now dammed for hydropower production, the occurrence of FPM glochidia was always highest on salmon. Moreover, glochidia on salmon were often larger than the conspecifics on brown trout. Conversely, in small tributaries with no salmon history, brown trout was generally the best, or the only suitable, host for FPM. The adaptation of certain FPM populations to salmon is a highly significant finding, which offers — together with the hydropower dam construction and the salmonid stocking practices that often favour brown trout — an explanation for the collapse of FPM populations living in former Atlantic salmon rivers. This study illustrates the indirect but substantial effects that dams and changes in fish communities may induce, and emphasises the need to determine the most suitable host species for each FPM population in order to inform conservation and management actions.